Crecimiento en diámetro y altura total en las plantas de Swietenia macrophylla King “caoba” con diferentes dosis y frecuencia de fumigación del fertilizante foliar en plantación, Puerto Almendra, Loreto, Perú – 2021 - Calderón Glaston, Rosa Noruska (2024)
The study was carried out at CIEFOR Puerto Almendra – FCF – UNAP, San Juan Bautista district, Maynas province, Loreto region. The objective was to determine growth in diameter and total height in Swietenia macrophylla King “caoba” plants with different doses and frequency of foliar fertilization in plantations at 5 years of age. The diameter and total height of the Swietenia macrophylla King “caoba” plants were evaluated. The result indicates that the greatest growth in total height was observed in the treatment: 20 ml of concentrate / 20 liters of water, applied 3 times per week with 177,3 cm and, in diameter, occurred in the Swietenia macrophylla King plants. “caoba” in the treatment: 60 ml of concentrate / 20 liters of water, applied 3 times a week with 18,5 mm.